ANALGETIC ACTIVITY OF SUBSTITUTED 1-(2-IMIDAZOLETHYL)-3- PYRROLINE-2-ONS - A. A. Ponomaryova; A. S. Yurchenko; N. N. Kasimova (Фармация и фармакология (Пятигорск), 2015)
The article presents the review of initial stage of carried out studies of an analgetic activity of substituted 1-(2-imidazolethyl)-3-pyrroline-2-ons. We have established that compound marked with laboratory cipher as GKN-1165 at a dose of 50 mg/kg has analgetic activity close to the activity of ethanol of nimesulid comparison taken at the same dose.